Optimism's Impact on Quality of Life in Chronic Disease Patients: A Systematic Review - Yulis Andri Nuryani; Dewi Gayatri; Yati Afianti (Indonesian Journal of Global Health Research, 2025)
Chronic diseases have a significant impact on patients' quality of life, physically, psychologically and socially. Optimism, as part of positive psychology, plays an important role in helping patients face health challenges and improve their well-being. Objective: To identify the relationship between optimism and quality of life in patients with chronic diseases through a systematic review. Method: Following PRISMA 2020 guidelines, a comprehensive search across databases such as PubMed, Scopus, Sage, and Nature identified 7,340 articles, with six studies meeting the inclusion criteria. The review included only full-text, English-language quantitative studies—specifically case-control, cross-sectional, cohort, randomised controlled trials (RCTs), or quasi-experimental designs—that examined the relationship between optimism and quality of life in patients with chronic illnesses. There were no restrictions on publication year. Exclusion criteria comprised review articles, meta-analyses, and book or book chapter publications. Each included study was critically appraised using the CASP tool, which assessed research objectives, study design, sampling methods, measurement validity, bias control, and data analysis to ensure methodological rigour. Results: The analysis showed that optimism was positively associated with improved quality of life, especially in physical aspects such as reduced fatigue and improved mobility, as well as psychological aspects such as emotional and spiritual well-being. Social support also strengthened the impact of optimism on quality of life. Community-based interventions, occupational therapy, and multimodal approaches proved effective in increasing patient engagement in meaningful activities. Conclusions: Optimism is an important factor in improving the quality of life of chronic patients, and optimism-based interventions can be an effective strategy to support holistic patient well-being.